2006
DOI: 10.1186/1476-069x-5-31
|View full text |Cite
|
Sign up to set email alerts
|

Long-term consequences of arsenic poisoning during infancy due to contaminated milk powder

Abstract: Arsenic toxicity is a global health problem affecting many millions of people. The main source of exposure is drinking water contaminated by natural geological sources. Current risk assessment is based on the recognized carcinogenicity of arsenic, but neurotoxic risks have been overlooked. In 1955, an outbreak of arsenic poisoning occurred among Japanese infants, with more than 100 deaths. The source was contaminated milk powder produced by the Morinaga company. Detailed accounts of the Morinaga dried milk poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 17 publications
3
65
0
Order By: Relevance
“…However, the number of patients in Okayama Prefecture is reported to be 2,005, and at least 33,500 one-pound cans were consumed in Okayama [7]. Because the dose of poisoned milk powder needed to cause clinical poisoning in an infant corresponds to five cans [6], the number of possible acute poisonings in Okayama could, therefore, have been three times the official estimate. Because the size of a 5-year birth cohort in Okayama is approximately 150,000, this means that the number of clinically poisoned subjects may represent only 4% of the cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the number of patients in Okayama Prefecture is reported to be 2,005, and at least 33,500 one-pound cans were consumed in Okayama [7]. Because the dose of poisoned milk powder needed to cause clinical poisoning in an infant corresponds to five cans [6], the number of possible acute poisonings in Okayama could, therefore, have been three times the official estimate. Because the size of a 5-year birth cohort in Okayama is approximately 150,000, this means that the number of clinically poisoned subjects may represent only 4% of the cohort.…”
Section: Discussionmentioning
confidence: 99%
“…During early summer in 1955, mass arsenic poisoning of bottle-fed infants occurred in the western part of Japan because of contaminated milk powder [6]. Although the contaminated milk was announced as the cause of the poisoning and ordered to be recalled on August 24th, contamination continued for at least 4 months [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from human studies, lead exposure during early stages of the rat brain development has been suggested to decrease protein kinase C (PKC) activities and also to reduce PKC isoforms including PKC-γ and ε which are reported to have roles in memory formation and long-term potentiation 108) . Since early exposure to lead at the developmental stage, as well as to methylmercury and arsenic [109][110][111][112][113] , can produce lifelong loss of intelligence and permanent disruption of behavior 114) , special attention should be directed to food and water safety for younger children and mothers.…”
Section: Lead Toxicity In Childrenmentioning
confidence: 99%
“…The incident became known as the "Morinaga dried milk poisoning". By 2002, there were an estimated 13 400 cases and over 100 deaths attributed to consumption of the milk powder (Dakeishi et al 2006). Incidents related to food security are reported almost every year from all over the world.…”
mentioning
confidence: 99%